Formamides as Lewis Base Catalysts in SN Reactions—Efficient Transformation of Alcohols into Chlorides, Amines, and Ethers. Issue 34 (4th July 2016) - Huy, Peter H.; Motsch, Sebastian; Kappler, Sarah M.
Abstract: A simple formamide catalyst facilitates the efficient transformation of alcohols into alkyl chlorides with benzoyl chloride as the sole reagent. These nucleophilic substitutions proceed through iminium‐activated alcohols as intermediates. The novel method, which can be even performed under solvent‐free conditions, is distinguished by an excellent functional group tolerance, scalability (>100 g) and waste‐balance (E‐factor down to 2). Chiral substrates are converted with excellent levels of stereochemical inversion (99 %→≥95 % ee ). In a practical one‐pot procedure, the primary formed chlorides can be further transformed into amines, azides, ethers, sulfides, and nitriles. The value of the method was demonstrated in straightforward syntheses of the drugs rac ‐Clopidogrel and S ‐Fendiline. Abstract : A simple formamide catalyst enables highly efficient dehydroxychlorinations of alcohols with benzoyl chloride as the sole reagent. The novel method, which proceeds through iminium‐activated alcohol intermediates, exhibits an excellent functional group tolerance, scalability and waste‐balance. Enantioenriched alcohols (99 % ee ) are converted under inversion into the corresponding chlorides (≥95 % ee ).